Perkawinan Beda Agama dalam Perspektif Hukum Positif di Indonesia - Daeng Tarring, Anisah (Jurnal Litigasi Amsir, 2022)
Interfaith Marriage in a Positive Legal Perspective in Indonesia. This study aims to determine, and analyze the legitimacy of interfaith marriages in terms of marriage laws that apply in Indonesia and analyze what legal consequences arise in marriages of Indonesian citizens with foreign citizens of different religions. This study uses a normative juridical approach. A juridical approach is used to analyze various principles and theories related to the problems studied. The results of the study show that the validity of marriage in Indonesia cannot be separated from religious law, where interfaith marriages are seen from Islamic religious law and Christian religious law and other religions, basically it is not allowed to be carried out, so that if there are interfaith marriages carried out, the marriage is considered invalid. The legal consequences arising from interfaith marriages are the juridical and psychological aspects. Which is where if this interfaith marriage occurs, its legality is not recognized both in formal juridical and religious terms. Then from the psychological aspect of marriage which results in the status and belief of children, because in Indonesia they consider a legitimate child to be a child born from a legal marriage.